Research and Practice of Blended Teaching Mode of Ideological and Political Course in Higher Vocational Colleges - Qian Zhang (Forest Chemicals Review, 1970)
In the new period, a higher requirement is put forward for the comprehensive quality of modern talents. Faced with this brand-new demand for personnel training, higher vocational colleges, as the main front for the cultivation of professional and skilled personnel in China, must establish their brand-new concept of personnel training and strengthen the cultivation of students' total quality in the course of paying attention to the teaching of students' professional knowledge and skills. As the ideological and political course is an important course to implement the cultivation of students' ideological and moral quality in higher vocational education, it is necessary to promote the all-round evolution of students by strengthening the exploration of the teaching effectiveness of this course, In view of the general trend, ideological and political educators in colleges and universities combine the development of the 21st century and actively explore more efficient ideological and political models in order to improve the advancement and effectiveness of ideological and political progress. This article mainly analyzes the construction of a mixed teaching model Realize the optimization and innovation of ideological and political education in higher vocational colleges.